2002
DOI: 10.1074/jbc.m107716200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of FTDP-17 tau Gene Mutations through Their Effects on Xenopus Oocyte Maturation

Abstract: tau gene mutations cause frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17). Here we have used Xenopus oocyte maturation as an indicator of microtubule function. We show that wildtype four-repeat Tau protein inhibits maturation in a concentration-dependent manner, whereas three-repeat Tau has no effect. Of the seven four-repeat Tau proteins with FTDP-17 mutations tested, five (G272V, ⌬K280, P301L, P301S, and V337M) failed to interfere significantly with oocyte maturation, demonstrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 46 publications
7
29
1
1
Order By: Relevance
“…As previously described [5], oocyte injection of 50 ng htau412 did not interfere with maturation (Fig. 1A).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…As previously described [5], oocyte injection of 50 ng htau412 did not interfere with maturation (Fig. 1A).…”
Section: Resultssupporting
confidence: 82%
“…Recombinant Tau proteins or bu¡er alone were microinjected in oocytes at a constant volume of 50 nl per stage VI oocyte by the use of a positive displacement digital micropipette (Nichiryo) as previously described [5].…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…Western blot analyses using a panel of phosphorylation-dependent anti-tau antibodies demonstrate a selective and dramatic reduction in the phosphorylation of Ser396 and Ser404, consistent with previously published studies (data not shown) Perez et al, 2000;Sahara et al, 2000;VogelsbergRagaglia et al, 2000, Delobel et al, 2002. Finally, human tau serially extracted from the spinal cord of RW and hWT mice also showed a similar age-related increase in insoluble tau and reduction in Ser396 -Ser404 phosphorylation (data not shown).…”
Section: Rw Tau Showed An Increased Accumulation Of Insoluble Tau Andsupporting
confidence: 78%
“…Some of these mutations (e.g., P301L) also facilitate the pathological fibrillogenesis of tau (Hasegawa et al, 1998;Hong et al, 1998;Bugiani et al, 1999;D'Souza et al, 1999;Murrell et al, 1999;Rizzu et al, 1999;Barghorn et al, 2000;Pickering-Brown et al, 2000;Rizzini et al, 2000). Finally, several tau gene mutations, most notably R406W, alter the phosphorylation state and solubility of tau, thereby contributing to the formation of fibrillary tau aggregates (Lee et al, 1991;Crowther and Goedert, 2000;Perez et al, 2000;Sahara et al, 2000;Vogelsberg-Ragaglia et al, 2000;Connell et al, 2001;Delobel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…L'étude in vitro de l'effet des mutations non-sens du premier groupe montre que les protéines tau mutées se lient moins aux microtubules et ne permettent pas une bonne polymérisation de la tubuline en microtubules. Cela a été récem-ment vérifié in situ, montrant que la plupart des mutations non-sens, à l'exception de la mutation R406W, ne modifient pas la phosphorylation des protéines tau mais bien leur liaison aux microtubules [23]. Lorsque la mutation est située dans la région exonique commune aux six isoformes, et en dehors de l'exon 10 (G272V, V337M), les six isoformes perdent leur fonctionnalité.…”
Section: Les Protéines Tau Normalesunclassified